2009
DOI: 10.3922/j.psns.2009.2.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing executive functions in older adults: A comparison between the manual and the computer-based versions of the Wisconsin Card Sorting Test.

Abstract: Executive functions (EF) are a group of high-level cognitive processes that control and direct lower-level abilities in order to produce goal-directed behavior. Because these functions are a multidimensional entity, they can be assessed using different tests. One of the tests often used to evaluate EF is the Wisconsin Card Sorting Test (WCST). The WCST is a task that involves hypothesis testing, identification of concepts, resistance to interference, switching categories, and inhibition. Two versions of the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Several researchers had the objective of verifying the equivalence between traditional and computerized tests. Studies by Collerton et al ( 6 ) and Wagner and Trentini ( 7 ) observed the equivalence between the two methods; whereas the studies by Feldstein et al ( 8 ) and Steinmetz et al ( 9 ) showed a difference in the results suggesting that skills to use computers might favor a better performance of the person assessed. The study done by McDonald et al ( 10 ) showed a yet greater difference in the elderly population.…”
Section: Introductionmentioning
confidence: 96%
“…Several researchers had the objective of verifying the equivalence between traditional and computerized tests. Studies by Collerton et al ( 6 ) and Wagner and Trentini ( 7 ) observed the equivalence between the two methods; whereas the studies by Feldstein et al ( 8 ) and Steinmetz et al ( 9 ) showed a difference in the results suggesting that skills to use computers might favor a better performance of the person assessed. The study done by McDonald et al ( 10 ) showed a yet greater difference in the elderly population.…”
Section: Introductionmentioning
confidence: 96%
“…Computerized adaptations of existing tests may not have the same psychometric properties as pencil‐and‐paper versions, and thus, require their own validation studies. In addition, few studies have found substantive evidence to support the equivalence between the experience of computer and noncomputer methods of test administration from the patient perspective [2,7]. Finally, computerized assessments raise issues related to the impersonal nature of testing, in particular at a time when end‐users may feel vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fact, the main manuals of neuropsychology caution against using WCST results isolatedly as a marker of damage in the frontal lobe, hence recommending convergent measures of assessment (Lezak, Howieson, & Loring, 2004;Strauss, Sherman, & Spreen, 2006). specific population, such as elderly (Beckert, Irigaray, & Trentini, 2012;Wagner & Trentini, 2009) and murderers (Del Pino & Werlang, 2008).…”
Section: Introductionmentioning
confidence: 99%